Implementing the TOPSIS Method for Book Update and Procurement Priority - Tamsir, Nurlindasari; Magfirah, Magfirah; Rosida, Vivi; H. Umar, St. Amina; Widyawati, Widyawati (Program Studi Teknik Elektro Universitas Khairun, 2025)
A library is a building or room designed for the purpose of storing and organizing various types of library items, including books, monographs, serial publications, brochures, and non-library materials. In the Hasanuddin University (Unhas) library, there are at least 516,000 volumes of literature. One of the important things is how to ensure that the contents of the library remain relevant to the special literacy needs of this modern era. Considering that books are static, of course it is necessary to update and procure the newest and most up-to-date types of books. The goal of this research is to use the TOPSIS algorithm to determine the procurement and updating of books in the UNHAS library, particularly at the Faculty of Nursing. Based on the regular year data criteria (2008–2023), it is known that books borrowed (5–25≤ ) and book stocks (5–45 copies) are based on the publication every five years. It is known that if the preference value (v) 0.60 is included in the procurement category, preference (v) 0.30 is included in the updating category, and preference (v) 0.31–0.59 is not included in the procurement and update categories. The ranking results of 6 (six) book samples reveal that 2 (two) categorized into the procurement category with a preference value (v) of 0.64, 2 (two) categorized into the updating category with a preference value (v) of 0.2 and 0.3, and 2 (two) categorized into the category where book updates and procurement do not occur, with preference values (v) of 0.36 and 0.5.